ANALISIS PENENTUAN HARGA POKOK PRODUKSI PADA UMKM PENGOLAHAN MIE BASAH DI BANJARMASIN - Isa Parrahullah; Monry Fraick Nicky Gillian Ratumbuysang (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
This research aims to 1) Find out how UD. Mie Putra Solo, Mie Basah Aceng, and Mie Cap Burung Elang in determining the cost of production; 2) Knowing the determination of the cost of production at UD. Mie Putra Solo, Mie Basah Aceng, and Mie Cap Burung Elang using the full costing method. This type of research is quantitative descriptive with primary and secondary data sources collected through interviews and documentation, then analyzed using the Miles and Huberman model. The resource person for this research was UD. Mie Putra Solo, Mie Basah Aceng, and Mie Cap Burung Elang. The research results show that 1) The method of determining the cost of production carried out by UD. Mie Putra Solo, Mie Basah Aceng, and Mie Cap Burung Elang are still very simple using traditional methods. The calculation does not use a method for determining the cost of production in accordance with cost accounting principles, there are elements of factory overhead costs such as depreciation of fixed assets that are not taken into account, and there is no classification of production costs; 2) The researcher carried out the calculation of the cost of production using the full costing method by classifying costs according to type and taking into account all elements of production costs. The result is that the cost of production is higher than the MSME calculation, due to the addition of factory overhead costs such as depreciation of fixed assets which were previously not taken into account by the MSME.